Evaluacion de herbicidas sulfonilureas para el control de malezas en cafetales - Anzalone, A.=700 1 Silva, A.
(Es, En)
Ilus., 24 ref
Keywords: COFEA ARABICA; MALEZAS; ESCARDA; CONTROL QUIMICO; HERBICIDAS; NICOSULFURON; GLIFOSATO; VENEZUELA; BIOAGRO